How Does Palestinian Popular Culture Shape and Influence Leadership Imagery? - Atef, Raed (Cultural Arts Research and Development, 2026)
This study explores how Palestinian proverbs shape leadership imagery within a sociopolitical context defined by resistance, occupation, and national struggle. Drawing on an interdisciplinary cultural studies framework, it examines proverbs not merely as linguistic expressions but as symbolic, aesthetic, and performative artifacts that communicate collective values and political ideals. Through qualitative interpretive analysis of documented proverb collections, scholarly literature, visual materials, and media representations, the research identifies key thematic categories linking leadership to land, honor, resistance, unity, power, and moral conduct. Findings reveal that Palestinian proverbs function simultaneously as moral texts and political commentaries, articulating expectations of leadership grounded in sacrifice, stewardship of land, strategic pragmatism, and social accountability. Sayings related to attachment to land frame leadership legitimacy through ethical responsibility and collective dignity, while proverbs addressing resistance emphasize resilience and cohesion. Other expressions critically interrogate corruption, patronage, and internal fragmentation, demonstrating how popular culture both legitimizes and scrutinizes authority. By integrating textual and visual analysis, the study highlights how proverbs circulate across speech, art, and education to reinforce leadership ideals at the grassroots level. The research contributes to leadership and cultural studies by foregrounding indigenous oral traditions as dynamic sites of political imagination and symbolic power, showing how popular culture shapes leadership narratives in contexts of prolonged struggle and resistance.